Pengaruh Rancangan Muffler Terhadap Peredaman Suara Dan Unjuk Kerja Mesin - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Muffler is very importance to reduce engine noise (because of the exhaust gas). A Good Muffler (for reducing noise) usually have a bad effect for the engine performance. This experiment have a target to get the optimal muffler for the stationary gasoline engine with variation of the load and the engine speed. In this experiment used 6 design of the muffler and the result shown that variation of the muffler design haven't significant effect to the engine performance. If compare to engine condition without muffler,using muffler will reduce engine torsion and the fuel consumption will increase. With using muffler, we have the significant noise reduction.